2020
DOI: 10.1101/2020.02.05.936187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A glucose starvation response governs endocytic trafficking and eisosomal retention of surface cargoes

Abstract: Eukaryotic cells adapt their metabolism to the extracellular environment. Downregulation of surface cargo proteins in response to nutrient stress reduces the burden of anabolic processes whilst elevating catabolic production in the lysosome. We use yeast to show that glucose starvation triggers a transcriptional response that simultaneously increases internalisation from the plasma membrane whilst supressing recycling from endosomes back to the surface. Nuclear export of the Mig1 transcriptional repressor in r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…Yet, not only substrate transport can induce nutrient transporter endocytosis, but also nutrient limitation, acute starvation or rapamycin treatment ( Crapeau et al, 2014 ; Hovsepian et al, 2017 ; Jones et al, 2012 ; Laidlaw et al, 2020 ; Lang et al, 2014 ; Müller et al, 2015 ; Schmidt et al, 1998 ; Yang et al, 2020 ). Starvation-induced endocytosis is part of a coordinated catabolic cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, not only substrate transport can induce nutrient transporter endocytosis, but also nutrient limitation, acute starvation or rapamycin treatment ( Crapeau et al, 2014 ; Hovsepian et al, 2017 ; Jones et al, 2012 ; Laidlaw et al, 2020 ; Lang et al, 2014 ; Müller et al, 2015 ; Schmidt et al, 1998 ; Yang et al, 2020 ). Starvation-induced endocytosis is part of a coordinated catabolic cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that in response to glucose starvation, the yeast AP180 clathrin adaptors are transcriptionally upregulated with a concomitant increase in endocytosis (Laidlaw et al, 2020). Under basal conditions in media lacking methionine, the methionine transporter Mup1 tagged with GFP localises to the plasma membrane (PM), but much of this signal is redistributed to endosomes and the vacuole upon plasmid over-expression of mCherrytagged AP180s: Yap1801-Cherry or Yap1802-mCherry (Figure 1A).…”
Section: Glucose Starvation Inhibits Surface Recyclingmentioning
confidence: 97%
“…Similarly, we find shifting cells to media lacking sugar or supplemented with raffinose also results in robust inhibition of recycling (Figure 1D). Therefore, although internalization from the plasma membrane increases following glucose starvation (Laidlaw et al, 2020), two dedicated recycling reporters show glucose starvation also triggers a reduction in protein and lipid traffic from endosomes back to the PM. We propose increased internalization and decreased recycling during glucose starvation cooperate to drive vacuolar degradation of cargoes en masse in response to nutritional stress.…”
Section: Glucose Starvation Inhibits Surface Recyclingmentioning
confidence: 99%
See 2 more Smart Citations